2012
DOI: 10.1016/j.vetpar.2011.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Preserving new anthelmintics: A simple method for estimating faecal egg count reduction test (FECRT) confidence limits when efficacy and/or nematode aggregation is high

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 As it has been 30 years since a new anthelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 51 publications
0
52
0
3
Order By: Relevance
“…In this case the UI of the percentage reduction are 98.0% to 100%. The method previously described by Dobson et al (2012) attempts to address the problem of uncertainty intervals for such observations with a mean of zero epg, an issue earlier techniques such as the RESO method cannot address (Excel version of RESO available at http://sydney.edu.au/vetscience/sheepwormcontrol/software/FECR4.xls).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case the UI of the percentage reduction are 98.0% to 100%. The method previously described by Dobson et al (2012) attempts to address the problem of uncertainty intervals for such observations with a mean of zero epg, an issue earlier techniques such as the RESO method cannot address (Excel version of RESO available at http://sydney.edu.au/vetscience/sheepwormcontrol/software/FECR4.xls).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed solution of Dobson et al (2012) uses the raw observed egg count and the inverse beta distribution. However this method is unable to generate rational UI for the FECR when the efficacy is poor or if the observed post-treatment egg counts are higher than pre-treatment counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timeliness and relevance of our results are indicated by the recent literature published on the topic (Denwood et al 2010;Levecke et al 2011;Dobson et al 2012;McKenna 2013), highlighting the urgency to reach a consensus as to which calculation method should be used. Shortly after the World Association for the Advancement of Veterinary Parasitology (WAAVP) endorsed FECR 4 as the standardized method of calculation (Coles et al 1992), a second set of WAAVP-endorsed guidelines, recommending the use of geometric means, were published by Wood et al (1995).…”
Section: Discussionmentioning
confidence: 68%
“…Shortly after the World Association for the Advancement of Veterinary Parasitology (WAAVP) endorsed FECR 4 as the standardized method of calculation (Coles et al 1992), a second set of WAAVP-endorsed guidelines, recommending the use of geometric means, were published by Wood et al (1995). The latter guidelines were criticized by McKenna (1997) and Van Wyk and Groeneveld (1997), and since that time there has been an ongoing discussion as to which method is more appropriate (Denwood et al 2010;Dobson et al 2012).…”
Section: Discussionmentioning
confidence: 99%